The Effectiveness of Kersen (Muntingia calabura linn.) Tea as Functional Drinks to Decrease Blood Glucose Level - Nairfana, Ihlana; Suter, I Ketut; Harsojuwono, Bambang Admadi (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology), 2020)
The aim of this research was to find the best treatment in order to achieve kersen tea with the highest flavonoid content and was expected to decrease blood sugar levels. This research was conducted in three stages. Stage I was qualitative anylisis of flavonoids, the leaf position, different flavonoids extraction condition whether it was extracted in daylight or dark condition, and the sample:solvent ratio that gives the highest flavonoids contents. Stage II was to find out the effect of temperature and drying time on total flavonoids, antioxidant activity, and hedonic test for color, taste and aroma. Stage III was in-vivo test to determine the ability of kersen leaf tea to reduce blood sugar levels in hyperglycemic mice. Kersen leaves positively contained flavonoids after tested in quantitative and qualitative ways. Sample from middle leaves that was dried at 60oC for 60 minutes and was extracted in daylight condition with the sample:solvents ratio of 1:10 gives the highest flavonoids contents (7,75 mg/g extract), highest antioxidant activity (IC50 of 54,82 ppm), and tea color that was preferred by panelist. Kersen tea was able to decrease high blood sugar level of hyperglycemic BALB/c mice from 272.1 mg/dL to 250.2 mg/dL, or by 8.04%.